Molecular surface functionalization to enhance the power output of triboelectric nanogenerators. Issue 10 (11th February 2016) - Wang, Sihong; Zi, Yunlong; Zhou, Yu Sheng; Li, Shengming; Fan, Fengru; Lin, Long; Wang, Zhong Lin
Abstract : For the enhancement of triboelectric nanogenerator's output performance, the method of using self-assembled monolayers to functionalize surfaces is introduced. Abstract : Triboelectric nanogenerators (TENGs) have been invented as a new technology for harvesting mechanical energy, with enormous advantages. One of the major themes in their development is the improvement of the power output, which is fundamentally determined by the triboelectric charge density. Besides the demonstrated physical surface engineering methods to enhance this density, chemical surface functionalization to modify the surface potential could be a more effective and direct approach. In this paper, we introduced the method of using self-assembled monolayers (SAMs) to functionalize surfaces for the enhancement of TENGs' output. By using thiol molecules with different head groups to functionalize Au surfaces, the influence of head groups on both the surface potential and the triboelectric charge density was systematically studied, which reveals their direct correlation. With amine as the head group, the TENG's output power is enhanced by ∼4 times. By using silane-SAMs with an amine head group to modify the silica surface, this approach is also demonstrated for insulating triboelectric layers in TENGs. This research provides an important route for the future research on improving TENGs' output through materials optimization.